Design of an inclined weight measurement system for prosthetic arm innovation - Tran, Dang Khoa; Nguyen, Thanh Hai (Journal of Technical Education Science, 2019)
Force feedback is one of the top critical aspects of prosthetic solutions. For patients equipped with powered prosthetic arms, their ability to grasp, manoeuvre and feel heavy objects is limited at rest and during exercises. This research approaches a solution that may help to solve the problem for many patients – a prototype capable of measuring the weight of objects automatically at multiple degrees of freedom of the patient’s prosthetic arm. By incorporating the existing technologies of a micro-electromechanical system capacitive accelerometer with a strain gauge force transducer, the weight of an object is measurable instantly the moment it is held, independent of any inclination. Results showed that the weight of an object measured at different 90o movement angles is similar to the actual weight of the object in use. The mean measurement error is approximately ±0.05kg of the tested object’s mass of 1.5kg at multiple inclines. Not only the result showed a positive outcome which fulfilled the objectives of the research, but it is also a deciding factor for developing the technology further. Apart from helping to improve patients’ sensory feedback, one of its top applications in healthcare is monitoring patient prosthesis-compatibility during heavy exercises.